2011
DOI: 10.1021/ol203185f
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of seco-Plakortolide E and (−)-ent-Plakortolide I: Absolute Configurational Revision of Natural Plakortolide I

Abstract: A first total synthesis of (-)-ent-plakortolide I and seco-plakortolide E was accomplished from (S)-2-methylglycidol. The relevant key reactions involve a diastereoselective Mukaiyama aldol reaction, a regioselective hydroperoxysilylation, and elaboration of the 1,2-dioxane ring by intramolecular Michael addition of a hydroperoxide group to a butenolide. This synthesis allowed the revision of the absolute configuration of plakortolide I and structural revision of plakortolide E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…7 The first total synthesis of seco-plakortolide E also supported the structural revision of plakortolide E. 8 Continuing investigation of the same sponge, P. clathrata, afforded an additional set of 16 plakortolide metabolites 10-25. 9 A Jamaican collection of Plakinastrella onkodes yielded two cyclic peroxides, plakortolide F 26 and plakortolide G 27.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…7 The first total synthesis of seco-plakortolide E also supported the structural revision of plakortolide E. 8 Continuing investigation of the same sponge, P. clathrata, afforded an additional set of 16 plakortolide metabolites 10-25. 9 A Jamaican collection of Plakinastrella onkodes yielded two cyclic peroxides, plakortolide F 26 and plakortolide G 27.…”
Section: Introductionmentioning
confidence: 82%
“…11 Two 1,2-dioxane peroxylactones, plakortolides H and I 29 and 30, have been isolated from a Madagascar specimen of Plakortis aff simplex, both of which were cytotoxic against a range of human tumour cell lines. 12 Several years later, the relative and absolute configurations of plakortolide I were revised on the basis of synthetic studies and reassignment of the NMR data, 8,13 thereby establishing that the metabolite isolated was ent-plakortolide I 31. Whilst the trivial name plakortolide I has been proposed for an unnamed plakortolide metabolite 32 from the Philippine Sponge Plakinastrella sp., whose absolute stereochemistry was determined by application of Mosher's method to a derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent DIBAL-mediated reduction of the lactone, followed by addition of excess trimethylsilyl triate resulted in simultaneous deprotection of the peroxide group and cyclisation to the target cycloperoxides. Similar synthetic strategies have been employed by Vatèle in the rst total synthesis of seco-plakortolide E and (À)-ent-plakortide I 18 and for the total synthesis of andavadoic acid, a naturally occurring ve-membered ring peroxide. 19 Isayama demonstrated that the combination of Co(acac) 2 and TBHP efficiently promoted the peroxidation of a,b-unsaturated carboxylic acids and esters (Table 5).…”
Section: Isayama-mukaiyama Reactionmentioning
confidence: 96%
“…This included Baylis-Hillman products bearing O-protected groups (entries 8-10). A range of aldehyde substrates were also tolerated including aromatic (entries 11-15), heteroaromatic (entries [16][17][18] and aliphatic aldehydes (entry 19). The transformation of formamides (entry 20) was similarly successful.…”
Section: Kharasch and Related Reactionsmentioning
confidence: 99%
See 1 more Smart Citation